Transformational Leadership and Leaders’ Mode of Care Reasoning - Simola, Sheldene; Barling, Julian; Turner, Nick (2012)
Previous research on the moral foundations of transformational leadership has focused primarily on stage of justice reasoning; this study focuses on developmental mode of care reasoning. Multilevel regression analyses were conducted on data coded from interviews with a sample of Canadian public sector managers (N = 58) and survey responses from their subordinates (N = 119). Results indicated that managers’ developmental mode of care reasoning significantly and positively predicted subordinates’ reports of transformational (but not transactional) leadership, with significant differences in follower reports of transformational leadership between those using more versus less advanced modes of care reasoning. Conceptual implications for understanding transformational leadership and the ethics of leadership, directions for future research, and suggestions for leadership interventions are discussed.
Keywords: Transformational Leadership; Moral Reasoning; Leadership; Ethics; Care Ethics